UJI HOMOGINITAS DAN STABILITAS KANDIDAT BAHAN STANDAR ZIRKONIL KLORIDA (ZrOCL2) HASIL OLAH PASIR ZIRKON KALIMANTAN DENGAN METODE F-AAS THE HOMOGENEITY, AND STABILITY TEST OF ZIRCONYL CHLORIDE (ZrOCL2) PRODUCT FROM KALIMANTAN BY FLAME ATOMIC ABSORPTION SPE - Supriyanto C.; Samin Samin (Website, 2014)
Pembuatan bahan standar zirkonil klorida hasil olah pasir zirkon perlu dilakukan untuk mendukung kegiatan pilot plant pembuatan zirkonia di PTAPB-BATAN. Tujuan pembuatan bahan standar adalah untuk mengontrol kualitas produk zirkonia, validasi metode dan kalibrasi alat. Persyaratan yang harus dipenuhi sebagai kandidat bahan standar antara lain bahan tersebut homogen dan stabil, sehingga diperlukan uji homogenitas dan uji stabilitas. Uji homogenitas dan uji stabilitas dilakukan dengan metode statistik berdasarkan data kadar Zr dan Fe yang diperoleh secara F-AAS. Diperoleh nilai kepekaan dan presisi alat uji yang memenuhi persyaratan, masing-masing dengan kepekaan 0,019 ppm (persyaratan 0,040 ppm), dan presisi 0,762 % (persyaratan 1 %). Berdasarkan perhitungan statistik menggunakan uji F diperoleh harga F hitung pada kadar Zr dan Fe masing-masing 0,389 dan 2,903. Karena harga F hitung < harga F tabel (= 3,779), maka dapat disimpulkan bahwa kandidat bahan standar sudah homogen. Diperoleh nilai selisih antara rerata hasil uji kedua dan rerata hasil uji homogenitas (Xi–Xhm) masing-masing 0,0349 dan 0,2645. Sedangkan nilai dari 0,3 x nIQR (0,3 tetapan APLAC, nIQR adalah selisih kuartil 3 dan 1 yang ternormalisasi) masing-masing 0,0551 dan 0,2774. Harga (Xi–Xhm) < 0,3 (nIQR), maka dapat disimpulkan bahwa kandidat bahan standar sudah stabil. Kadar Zr yang diperoleh dengan metode F-AAS bila dibandingkan dengan kadar Zr yang diperoleh dengan metode XRF pada signifikansi 1 % menunjukkan harga t0 < t tabel (2,37 < 3,169), sehingga dapat disimpulkan tidak ada perbedaan rerata hasil antara kedua metode uji.In order to support the pilot plant of zirconia production at PTAPB-BATAN, standard materials of zirconyl chloride is absolutely needed. The aim of preparation of standard materials to be used to control the quality product of zirconia, validation the method, and for calibration instruments. Homogeneity and stability of sample play an important role in the fulfillment of candidate standard materials zirconyl chloride production requirements. To test the homogeneity, and stability using statistically data processing based on the content of Zr and Fe element were obtained by flame atomic absorption spectrophotometry (AAS) method. In the calibration of AAS test equipment, the values of sensitivity and precision test equipment obtained meets the requirements, such as a sensitivity of 0.019 ppm (0.040 ppm requirement), and the precision of 0.762% (1% requirement). Based on the calculation using F test statistically data processing were obtained that the values of calculated F were Zr 0.3890, and Fe 2,9036 respectively. The obtained value of calculated F were smaller than F table, so that the sample of candidate standard material zirconyl chloride were homogeneous. At the stability test based on the content of Zr and Fe element, the values of the differences between the mean values of the second test and the mean of the homogeneity ( Xi - Xhm ) were 0.0349 and 0.2645 respectively. Whereas the value of 0,3 x nIQR (0.3 constanta from APLAC, nIQR were the difference in quartile 3 and quartile 1 were normalized) were obtained that 0.0551 and 0.2774 respectively. The value of ( Xi - Xhm ) were obtained smaller than the value of 0,3 x nIQR, so that the sample of candidate standard material zirconyl chloride were stable. The content of Zr element in sample of candidate standard material zirconyl chloride was obtained by F-AAS method to compaired with XRF method showed that at level of significant 5 % was obtained t0=2,37 > ttable =2.28, show that the difference of average concentration, but lower than at level of significant 1 % (ttable= 3.169). Based on calculation of statistically data processing were conclusied that the candidate of standard materials zirconyl chloride were homogeneous and stable. The results of comparative tests of Zr content with XRF method showed no difference in sigifikance 1 %.